Positional concerns through the life cycle: Evidence from subjective well-being data and survey experiments - Alpaslan Akay; Peter Martinsson (Institute for the Study of Labor (IZA), 2012)
This paper uses both subjective well-being and survey experimental data to analyze how people's positional concerns regarding income and goods vary with age. The subjective well-being approach is mainly based on German panel data for the period 1984-2009 (German Socio-Economic Panel), while the survey experimental approach is based on a tailor-made experimental design conducted among Swedish adults. Our analysis suggests that the degree of positional concerns is not homogenous across the life cycle. Our different analytical approaches show a robust life cycle pattern of positional concerns: young people experience no or a low degree of positional concerns, yet the level of concerns for income increases gradually and significantly with age. The results also differ across goods: while car consumption is similar to income, the positional concern for leisure time decreases through the life cycle.
urn:nbn:de:101:1-201205026085
Keywords: C90; D63; 330; positional concerns; life cycle; subjective well-being; survey experiment; Sozialer Status; Lebensverlauf; Zufriedenheit; Schätzung; Deutschland; Feldforschung; Schweden